Microsurgical Treatment of Anterior Communicating Artery Aneurysms: A 20-year Single-institution Experience - Pietrantonio, Andrea; Trungu, Sokol; Delfini, Roberto; Raco, Antonino (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Anterior communicating artery (AComA) aneurysms are the most frequent intracranial aneurysms. They have a high risk of rupture, morbidity, and mortality following rupture. Surgical treatment is complex because of their deep location, proximity to the perforators, and their different projections and relations with the parent vessels. This retrospective study reports our experience in the surgical management of AComA aneurysms, describing how the microsurgical strategy is influenced by their projection and size, the orientation of the AComA complex, and the location and caliber of the parent vessels.Methods We reviewed all the patients treated surgically at our institution from September 1995 to March 2015 for ruptured and unruptured AComA aneurysms. Operative reports, neuroimages, and intraoperative videos were analyzed, and the surgical technique was examined. Illustrative cases are also included.Results A complete documentation was available for 223 (75.3%) of the 296 treated patients. Medium-size (55.1%) and superiorly projecting (31.8%) aneurysms were the most represented; 158 patients (70.9%) had different A1 diameters. A left- or right-sided pterional approach was performed in 85 patients (38.1%) and 138 patients (61.9%), respectively. A complete occlusion was documented in 185 patients (83%).Conclusions Posterior and superior projections are the most complex to deal with because of the difficult dissection of the perforators and the contralateral A2, respectively. Approaching from the side of the dominant A1 ensures a prompt proximal control. Searching preoperatively for an eventual rotation of the AComA complex and for the location of the A2s can be very helpful for intraoperative orientation.
Keywords: subarachnoid hemorrhage; AComA aneurysms; clipping; projections of the AComA aneurysms; side of approach